Dental anxiety in a students’ paediatric dental clinic: children, parents and students - BENJAMIN PERETZ, YARON NAZARIAN, & ENRIQUE BIMSTEIN (Paediatric Dentistry, 2004)
The purpose of the present study was to investigate the dental anxieties of children, parents and student caregivers in a dental school environment.